Sensory penalities: exploring the senses in spaces of punishment and social control - Herrity, Kate; Schmidt, Bethany E.; Warr, Jason (Emerald studies in culture, criminal justice and the arts, 2021)
Sensory Penalities reflects an explosion in explorations of the sensory and disrupts conventional expectations of both form and focus by expanding anthropological practices and craft into the field of criminology and criminological research. In providing accounts of physical/sensorial experiences within sites of surveillance and control, the authors in this edited collection bring elements of research experiences (often absent from existing work) to the fore; the impressions and sensual experiences which remain forever in field notes. In so doing they carve out spaces to consider these places and the ways in which they are theorised anew. The book aims to explore what sensory aspects of experience mean to those engaged in such research, and how they can shape our criminological thinking. What are the sensory textures of these experiences? What do they tell us? How do we communicate them? Finally, what does consideration of these elements tell us about penality? This timely volume challenges and remakes assumptions about what criminology is and should be; more accurately reflecting the post-disciplinary nature of the field.